BVBlue as a diagnostic instrument for the diagnosis of bacterial vaginosis: a systematic review - Igor Ian Wiguna; Kevin Tanoto; Valencia Hadinata; Nadir Chan; Budi Iman Santoso (BMC Women's Health)
Abstract Background Bacterial vaginosis (BV) refers to an imbalance in normal vaginal flora, affecting approximately 50–60% of individuals engaging in high-risk sexual behaviors. BV diagnosis traditionally relies on Amsel’s criteria or Nugent’s scoring, but these methods are sluggishly effective, leading to delayed treatment. BVBlue, a swift point-of-care test, holds promise as a potential diagnostic tool for BV. This systematic review aims to evaluate the accuracy of the BVBlue criteria compared with Nugent’s scoring in diagnosing BV. Methods We conducted a systematic search using designated terms in PubMed, ProQuest, and Scopus to identify all studies reporting BVBlue in diagnosing BV. We subsequently screened and critically evaluated the journals via the QUADAS-2 Quality Assessment Tool. This systematic review has been registered in PROSPERO (no. CRD42024545022). Result Out of 19 studies identified in our research, five were ultimately included. The quality assessment results revealed that all the included studies had good quality and low risk of bias. BVBlue has a sensitivity ranging from 38% to 91.7% and a specificity ranging from 91 to 100% in diagnosing BV. Four studies endorsed the BVBlue scale because of its high sensitivity, specificity, and rapidity in diagnosing BV. However, one study advised against its use in certain populations with mixed vaginal infections because of its inability to detect variation in composition and diversity of vaginal bacterial flora, that may be sialidase-negative. Conclusion Our systematic review revealed that BVBlue is a promising diagnostic tool for BV because of its accuracy and speed. Nevertheless, additional research is essential, particularly in elucidating the bacterial epidemiology of BV in certain countries, to validate its diagnostic credibility thoroughly.